Analysis of the GEDSI Framework (Gender Equality, Disability, and Social Inclusion) in Public Space Access for Persons with Disabilities in Tanjungpinang City - Amanda Lovita; Dian Prima Safitri; Okky Rizki Azizi (Pencerah, 2026)
Despite the enactment of Tanjungpinang City Regional Regulation No. 4 of 2017 on the Rights of Persons with Disabilities, public spaces in the city including Taman Tepi Laut, Museum Sultan Sulaiman Badrul Alamsyah, and key pedestrian corridors remain largely inaccessible for persons with disabilities. This study analyzes the dynamics of public space accessibility policy in Tanjungpinang City using the Multiple Streams Framework (MSF) and the Gender Equality, Disability, and Social Inclusion (GEDSI) framework. A descriptive qualitative approach was employed, with data analyzed using Miles et al., (2014) interactive model and supported by NVivo-12 software. The findings reveal that all four GEDSI dimensions: access, participation, control, and benefit remain unfulfilled, constrained by both physical barriers and structural deficiencies in policy planning. From the MSF perspective, the three streams have yet to converge: the problem has been identified, policy instruments such as the Regional Regulation and Gender-Responsive Budgeting have been formulated, yet weak political support and limited public awareness prevent the policy window from opening optimally. These findings underscore that inclusive public space governance in Tanjungpinang requires substantive integration of GEDSI principles, stronger inter-agency coordination, and the active role of disability groups as policy entrepreneurs.